Isolation of F. novicida-Containing Phagosome from Infected Human Monocyte Derived Macrophages - Marecic, Valentina; Shevchuk, Olga; Ozanic, Mateja; Mihelcic, Mirna; Steinert, Michael; Jurak Begonja, Antonija; Abu Kwaik, Yousef; Santic, Marina (Frontiers in Cellular and Infection Microbiology, 2017)
Francisella is a gram-negative bacterial pathogen, which causes tularemia in humans and animals. A crucial step of Francisella infection is its invasion of macrophage cells. Biogenesis of the Francisella-containing phagosome (FCP) is arrested for ~15 min at the endosomal stage, followed by gradual bacterial escape into the cytosol, where the microbe proliferates. The crucial step in pathogenesis of tularemia is short and transient presence of the bacterium within phagosome. Isolation of FCPs for further studies has been challenging due to the short period of time of bacterial residence in it and the characteristics of the FCP. Here, we will for the first time present the method for isolation of the FCPs from infected human monocytes-derived macrophages (hMDMs). For elimination of lysosomal compartment these organelles were pre-loaded with dextran coated colloidal iron particles prior infection and eliminated by magnetic separation of the post-nuclear supernatant (PNS). We encountered the challenge that mitochondria has similar density to the FCP. To separate the FCP in the PNS from mitochondria, we utilized iodophenylnitrophenyltetrazolium, which is converted by the mitochondrial succinate dehydrogenase into formazan, leading to increased density of the mitochondria and allowing separation by the discontinuous sucrose density gradient ultracentrifugation. The purity of the FCP preparation and its acquisition of early endosomal markers was confirmed by Western blots, confocal and transmission electron microscopy. Our strategy to isolate highly pure FCPs from macrophages should facilitate studies on the FCP and its biogenesis.